The Decoupling of Managersâ Self-interest and Implementation Performance: An Agency Theory Perspective - Qiu, Yarong (2008)
This thesis focuses on how to minimize the self-interest of the managersâ behavior in strategy implementation (SI), to achieve principal-interest maximization. Agency theory is used to predict the related factors of managersâ behavior, and in order to fill the gaps of agency theory in Asian countries, especially in China, this thesis introduces Guanxi in China with supplements from telephone interviews in 50 companies. Additionally, it assumes the related factors of the SI managersâ self-interest, predicts their interrelationships, and develops a model based on these related factors.